Морфо-біологічні та популяційні особливості Cornus mas L. у Закарпатті - Melnichuk, O.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Modern area of Сornus mas L. in Transcarpathia is investigated. The condition of natural populations, their structure and variability of morphological characters are analyzed.